(untitled) (Bangladesh Journal of Plastic Surgery, 2014)
Extensive soft tissue defects following trauma, burn or after cancer surgery need coverage by flaps. Sometimes surrounding tissues are not healthy enough or quantity is not favorable to provide adequate pedicle flaps. Microvascular free flap can provide healthy tissue of adequate amount from distant area for those difficult situations.15 microvascular free flaps were performed from October 2011 to February 2013. Radial forearm free flap was done in 8 and Latissimusdorsi (LD) flap in 7 cases. 10 flaps done in foot, ankle & lower leg region (radial forearm-5, LD-5) and 5 flaps were done in face and scalp region (radial forearm-4, LD-1).12 flaps healed uneventfully with good coverage of the defect. Average ischemia time was 135 min (range 100-240 min) and average anastomosis time was 75 min (average 60-100 min). 2 flaps failed. There was necrosis of the tip of 2 LD and cumbersome swelling of the flap was found in 2 cases of LD flaps.Large soft tissue defect of body where local or regional flaps are not feasible; can be easily covered with free flaps. Its capacity to cover huge soft tissue defect has neutralizes its technical demand. Though complications are still high in our hands; can be reduced performing more number of cases. DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18242 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 33-37